2012
DOI: 10.1371/journal.pone.0047345
|View full text |Cite
|
Sign up to set email alerts
|

Role of Kras Status in Patients with Metastatic Colorectal Cancer Receiving First-Line Chemotherapy plus Bevacizumab: A TTD Group Cooperative Study

Abstract: BackgroundIn the MACRO study, patients with metastatic colorectal cancer (mCRC) were randomised to first-line treatment with 6 cycles of capecitabine and oxaliplatin (XELOX) plus bevacizumab followed by either single-agent bevacizumab or XELOX plus bevacizumab until disease progression. An additional retrospective analysis was performed to define the prognostic value of tumour KRAS status on progression-free survival (PFS), overall survival (OS) and response rates.Methodology/Principal FindingsKRAS data (tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
4
37
0
1
Order By: Relevance
“…In der MACRO-sowie auch der CAIRO3-Studie wurden vor Beginn der Erhaltungstherapie 6 Zyklen CAPOX (4,5 Monate) gegeben [1146,1147]. In der AIO KRK-0207-Studie folgte die Erhaltungstherapie einer über 6 Monate durchgeführ-ten Induktionstherapie [1148].…”
Section: Konsensunclassified
“…In der MACRO-sowie auch der CAIRO3-Studie wurden vor Beginn der Erhaltungstherapie 6 Zyklen CAPOX (4,5 Monate) gegeben [1146,1147]. In der AIO KRK-0207-Studie folgte die Erhaltungstherapie einer über 6 Monate durchgeführ-ten Induktionstherapie [1148].…”
Section: Konsensunclassified
“…Recently KRAS exon 2 genotype was reported as significantly affecting PFS and OS in patients treated with XelOx/BEV [55].…”
Section: C35 G > a Kras Mutation In Mcrc Patients: Prognostic Relevamentioning
confidence: 99%
“…Studies have found that patients with KRAS mutated tumors have a lower recurrence free survival and lower overall survival (OS) rate compared to patients with wild-type tumors [3,[5][6][7]. LDH is a metabolic enzyme that catalyzes the conversion of pyruvate to lactate under anaerobic conditions and is overproduced in cancer cells [8].…”
Section: Introductionmentioning
confidence: 99%